2017
DOI: 10.7324/japs.2017.70410
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Identification of Novel Phytochemical Leads as Macrodomain Inhibitors of Chikungunya Virus Using Molecular Docking Approach

Abstract: The outbreak of Chikungunya fever worldwide has raised a threat to human health and an economic burden on the affected countries. Currently, there is no cure for Chikungunya. The computational methods assist in identifying the drug leads for the target. This work reports the potential phytochemical inhibitors against a unique macro domain present in the conserved N-terminal region of Non-structural protein nsP3 of Chikungunya virus. Macro domain contributes a lot to viral fusion and replication. The shape base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Three-dimensional structures of ligands were obtained in two ways: by extracting information from various libraries (65%) [ 57 , 58 , 59 , 60 , 61 ] or by constructing a molecule using special software (35%) [ 62 , 63 , 64 , 65 , 66 ]. PubChem (62%) was the most frequently used database, while ZINC (15.0%) and ChemSpider (12.0%) were less common.…”
Section: Resultsmentioning
confidence: 99%
“…Three-dimensional structures of ligands were obtained in two ways: by extracting information from various libraries (65%) [ 57 , 58 , 59 , 60 , 61 ] or by constructing a molecule using special software (35%) [ 62 , 63 , 64 , 65 , 66 ]. PubChem (62%) was the most frequently used database, while ZINC (15.0%) and ChemSpider (12.0%) were less common.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, traditional herbal medicines and purified natural products may guide the development of novel antiviral drugs [18]. Numerous studies have suggested that natural products can directly inhibit the growth and replication of viruses and bacteria [19][20][21][22]; for example, cacao, which has broadspectrum antimicrobial/antiviral activity when ingested in human studies [23]. Curiously, honey bees are frequently observed in nature collecting various natural products, such as resins, and applying them to the nest environment.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, the macro domain of CHIKV nsP3 has been described as a potential target in the development of anti-alphavirus compounds ( Nguyen et al, 2014 ; Subudhi et al, 2018 ; Vijayasri and Hopper, 2017 ). Despite the interest in the macro domain of nsP3, there is a lack of in vitro or in vivo studies on drugs that bind to this region of nsP3.…”
Section: Introductionmentioning
confidence: 99%